PERKEMBANGAN DAN HAMBATAN REKSADANA SYARIAH DI INDONESIA: SUATU KAJIAN TEORI - Kandarisa, Nur Aini (Jurnal Akuntansi AKUNESA, 2014)
Development of syaria mutual funds is starting to rise from the previous year, although in its development still encountered some obstacles. In March 2013 when the development of the net asset value NAV reaches Rp.8, 540.46 million, which reflects the annual growth (CAGR) of 60%, development of syaria mutual funds is also indicated by the presence of 58 syaria mutual fund product, this shows that the product of the syaria mutual funds have started in known by investors than years before. The greater number of syaria mutual funds that offered by investment manager, so the investment opportunities in syaria mutual funds will be increase.Keywords: mutual funds, syaria mutual funds.